Informator / "Solidarność" Region Środkowo-Wschodni . no. 88, 1984 - "Solidarność" Region Środkowo-Wschodni ([s.n.], 1984)
Creation and circulation: Publication contains listing of titles of Polish underground press, mostly from Środkowo-Wschodni region